A lack of retrieval practice effects in children's recognition and recall memory of novel words during storybook reading - Knabe, Melina L.; Bredemann, Catherine A.; Vlach, Haley A. (Frontiers in Developmental Psychology, 2023)
Retrieval practice enhances adults' long-term memory over restudying (e.g., Roediger & Karpicke, 2006). However, it is less clear whether young children also benefit from retrieval practice. This study assessed whether retrieval practice could support children's novel word learning in the context of storybook reading. In Experiments 1-3, preschoolers (N = 167, RangeAge = 26-68 months) were presented with 10 novel word-object pairs across four consecutive storybook readings. Half of the children were read the storybook four times (i.e., SSSS), whereas the other half of the children were read the storybook once and were then asked to retrieve the novel words during the subsequent three readings (i.e., STTT). Children's recall and recognition memory for the novel words was tested after a 5-minute delay. Results revealed that although children had high retrieval success during learning, retrieval practice did not provide an advantage over re-reading for children's recall (Experiment 1), even when additional mapping and retrieval opportunities were provided (Experiment 2); that is, children who engaged in retrieval practice did not outperform children who re-read the storybooks. A retrieval practice effect also did not emerge in children's recognition memory of novel words (Experiment 3).Taken together, this study suggests that retrieval practice may only benefit young children under specific learning conditions. Future research should therefore consider characteristics of the learner and broader learning context to explain developmental differences in retrieval practice effects.